Time-varying markups: Empirical analysis of markups in Finnish industries - Pentti Forsman; Tuomas Saarenheimo; Marko Terviö (Bank of Finland, 1997)
In this study, we analyse variation of markups in Finnish industrial sectors, both between industries and over time.The study finds evidence that:Since the beginning the 1980s, practically every Finnish industrial sector has been able to extract a positive markup.The average industrial markup has apparently declined over time.In addition to the declining trend, there seems to be procyclical movement in markups.Despite of the decline in average markups, most industries maintained positive markups in 1995.The same reservations apply to these results as to corresponding macro-level analysis of markups, because the model relies on instantaneous adjustment of the factors of production. If, for any reason, firms are slow to adjust their factors to changes in demand conditions, it would bias our markup estimates upwards.Indeed, we believe this is the case, so we do not recommend giving too much weight to the level of our markup estimates.Rather, we wish to note that the estimated time path for industrial markups is generally plausible.Thus, the decline in markups since 1991 may partly explain Finland's unexpectedly low inflation in recent years.
URN:NBN:fi:bof-20140807639
Keywords: 330; markup; imperfect competition